1996
DOI: 10.1518/001872096778701962
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors of Comfort and Discomfort in Sitting

Abstract: We conducted a classification analysis to identify factors associated with sitting comfort and discomfort. The objective was to investigate the possible multidimensional nature of comfort and discomfort. Descriptors of feelings of comfort and discomfort were solicited from office workers and validated in a questionnaire study. From this study, 43 descriptors emerged. The 42 participants rated the similarity of all 903 pairs of descriptors, and we subjected the resulting similarity matrix to multidimensional sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
207
0
12

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(226 citation statements)
references
References 20 publications
7
207
0
12
Order By: Relevance
“…Zhang, Helander, and Drury (1996) reported in their study that participants reported comfort as being associated with well-being while discomfort was associated with soreness, pain, and tiredness. In order to address this complex concept and to corroborate the objective and subjective measures with defining comfort and discomfort, this study used a validated tool (Crane and Hobson 2002) adapted by the researchers for suitability in this study.…”
Section: Test Protocolmentioning
confidence: 98%
“…Zhang, Helander, and Drury (1996) reported in their study that participants reported comfort as being associated with well-being while discomfort was associated with soreness, pain, and tiredness. In order to address this complex concept and to corroborate the objective and subjective measures with defining comfort and discomfort, this study used a validated tool (Crane and Hobson 2002) adapted by the researchers for suitability in this study.…”
Section: Test Protocolmentioning
confidence: 98%
“…In the driving context it has successfully been used to assess noise (Kuwano et al, 1994, Takao & Hashimoto, 1994. According to Helander & Zhang (1997, Zhang, Helander & Drury, 1996) the concepts of comfort and discomfort are independent entities associated with different factors. Comfort is related to well-being and aesthetics whereas discomfort has to do with biomechanics and fatigue.…”
Section: Developing a Semantic Differentialmentioning
confidence: 99%
“…Discomfort is more associated with biomechanical factors that produce feelings of pain, numbness and stiffness. These feelings increase with time on task and fatigue (Zhang et al, 1996). Comfort is a very important parameter for automobile seat design.…”
Section: Introductionmentioning
confidence: 99%